Toxicological Impact of Cadmium and Copper Exposure in H. Exemplaris - Ojekunle, Opeyemi Oluwadamilola; Olatoregun, Damola; Good, Sonya; Sodipe, Ayodotun (Environmental Management and Sustainable Development, 2022)
Cadmium and Copper are both heavy metals of concern and toxic environmental contaminants. Due to copper’s excellent electrical conductivity, its most common use is in electrical equipment. Cadmium on the other hand, is not essential, although it is used majorly in batteries. Contamination with cadmium and copper metals stems mainly from anthropogenic activities but other natural sources also exist. Tardigrades are microscopic aquatic animals renowned for their tolerance towards extreme environmental conditions, this study is to investigate their tolerance towards heavy metals and how to ameliorate the potential hazardous effects with an antioxidant (Selenium). Antioxidants are substances that may protect the cells against the effects of free radicals, they are intimately involved in the prevention of cellular damage: the common pathway for cancer, aging, and some diseases. We hypothesized that Hypsibius exemplaris (H. exemplaris) has a low tolerance to a high concentration of toxicants and if Reactive Oxygen Species is released, some enzymatic pathways will be altered, but a certain concentration of Selenium will abate this effect, confirming the antioxidative capacity of Selenium. As was observed, cadmium and copper solutions increased Tardigrade sensitivity to oxidative stress as well as significantly reduced metabolism was observed. The produced reactive oxygen species was confirmed with fluorescence microscopy. Treating the exposed tardigrades with 0.5ppm of selenium using sodium selenite counteracted the cadmium and copper induced reactive oxygen species produced. The antioxidative enzymes produced were quantified using various assay methods. In conclusion, from an environmental perspective, selenium is a relevant antioxidant using the appropriate dosage.